2021
DOI: 10.1134/s0016793221060116
|View full text |Cite
|
Sign up to set email alerts
|

Modulational Interaction in a Dusty Plasma of Meteoroid Wakes

Abstract: This is a study of the possible modulational instability of electromagnetic waves in meteoroid wakes associated with the dust acoustic mode at altitudes of 80–120 km, which is a linear stage of modulational interaction. The parameters of meteoroid wakes at different altitudes in the Earth’s ionosphere are considered. It is shown that the charging of dust particles of meteoric matter creates conditions for the occurrence of dust acoustic waves. Dust acoustic disturbances are excited due to the modulational inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Assuming that (5) we thus obtain a cubic equation of the form (6) that has an unstable solution characterized by the growth rate of (7) Dispersion relation ( 3) is typical of LH waves propagating at angles Θ relative to the earth's magnetic field that satisfy the condition . The presence of exponent 1/6 in the last multiplier on the right-hand side of (7) means that excitation of discussed oscillations upon propagation of a meteoroid in the Earth's ionosphere for typical parameters of plasma in the meteoroid wake is characterized by the growth rate on the order of frequency ω LH0 ≡ of the LH resonance.…”
Section: Excitation Of Lh Wavesmentioning
confidence: 99%
See 1 more Smart Citation
“…Assuming that (5) we thus obtain a cubic equation of the form (6) that has an unstable solution characterized by the growth rate of (7) Dispersion relation ( 3) is typical of LH waves propagating at angles Θ relative to the earth's magnetic field that satisfy the condition . The presence of exponent 1/6 in the last multiplier on the right-hand side of (7) means that excitation of discussed oscillations upon propagation of a meteoroid in the Earth's ionosphere for typical parameters of plasma in the meteoroid wake is characterized by the growth rate on the order of frequency ω LH0 ≡ of the LH resonance.…”
Section: Excitation Of Lh Wavesmentioning
confidence: 99%
“…For example, the mechanism of generation of low-frequency radio noise during Perseid, Leonid, Genimid, and Orionid meteor showers is related to development of modulational interaction in dusty plasma of the Earth's ionosphere [1,2]. Modulational interaction is also import-ant for explanation of acoustic waves generated by meteor showers [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover different kinds of low-frequency waves like ion acoustic waves, dust acoustic waves, and dust ion acoustic waves have already been investigated by many scientists [1,[18][19][20][21]. One very interesting study by Morozova and Popel has described that dust acoustic waves are generated by the meteoric body and radio waves emitted by the meteor lead to a modulation instability in electromagnetic waves [22]. Also, Liang et al showed the difficulty to propagate of the electromagnetic waves in plasma shock waves [23].…”
Section: Introductionmentioning
confidence: 99%